The level of C.pneumoniae, Cytomegalovirus, and H.pylori antibody in a patient with coronary heart disease (Medical Journal of Indonesia, 2002)
At herosclerosis is still the chief cause of morbidity and mortality in developed nations. Even though in developed nations the modification of risk factors is able to reduce the prevalence rate of atherosclerosis, such reduction is starting to slow down. Such condition has stimulated researchers to identify environmental exposure, including infection, that can influence the process of atherosclerosis. This cross sectional study was conducted from March to August 1998, on 122 patients that clinically demonstrate coronary heart disease and have underwent cardiac catheterization, 92 males and 30 females with an average age of 55 years. Patients undergo clinical and laboratory evaluation (blood glucose, cholesterol, triglyceride, and antibody for C.pneumoniae. Cytomegalovirus, and H.pylori). We found a significant difference in cholesterol, triglyceride, and HDL levels in those with coronary stenosis and those without. However, we did not find a significant difference in the levels of C.pneumoniae, Cytomegalovirus, and H.pylori antibodies. This study is unable to conclude the influence of these antibodies on atherosclerosis, since in the non-stenosis group, we cannot eliminate the possibility of atherosclerosis, since the average age of study subject is 55 years. Studies on the interaction between infection and traditional risk factors as well as gender and nutrition is needed to find a clear answer of the influence of infection in atherosclerosis. (Med J Indones 2002; 11: 211-4)Keywords: Level of C.pneumoniae, Cytomegalovirus, H.pylori antibody, coronary heart disease.